Hospital-based chronic disease care model: protocol for an effectiveness and implementation evaluation. Issue 7 (22nd July 2020) - Sumner, Jennifer; Phua, Jason; Lim, Yee Wei
Abstract : Introduction: Novel and efficient healthcare approaches are needed to better serve increasingly older chronic disease patients. Many effective integrated chronic disease management strategies have emerged from the primary care sector. However, in many Asian and developing countries, primary care is underdeveloped, and patients prefer secondary-based services. The Integrated Generalist-led Hospital (IGH) care model is a new approach, which may be better suited for chronic disease patients in the local context. Methods and analysis: A hybrid type I study on the effectiveness and implementation of the IGH care model will be conducted. Implementation evaluation will be informed by the Consolidated Framework of Implementation Research (CFIR). Quantitative and qualitative data will be collected through in-depth interviews and focus group discussions with staff, a staff survey, patient interviews, clinical outcomes and cost data. Clinical outcomes include the length of stay, readmission, emergency room visit rate and mortality. Clinical outcomes will be summarised and compared with a propensity-matched 'usual care' group (derived from the general medicine ward(s) at a separate hospital). The Kaplan-Meier approach will be used to estimate time until death and time until first readmission (both within 30 days of discharge) and time until discharge. Multivariate regression models will be used to investigate the association between the care model and occurrence of readmission, emergency room visit and death, all within 30 days of discharge. Qualitative data will be analysed using a thematic analysis method. Qualitative and quantitative data will also be coded according to the five domains of the CFIR. Ethics and dissemination: This protocol was reviewed and approved by the National Healthcare Group Domain Specific Review Board (NHG DSRB 2019/00308). Results will be published in peer-reviewed scientific journals and conference presentations. Findings will also be discussed with key stakeholders through local dissemination events.